External Characterization of Female Bali Cattle Populations In Gorontalo, Indonesia - Kamaru, Moh. Aditya; Dako, Safriyanto; Nugroho, Tri Ananda Erwin (Jurnal Sain Peternakan Indonesia, 2025)
The study aims to characterize female Bali cattle morphometric and phenotype in the Bone Raya sub-district, Bone Bolango district, Gorontalo, Indonesia. The research was conducted at four locations (Alo, Mootayu, Mootawa, and Mootinelo villages) from January to April 2023. A total of 64 Bali cattle aged 4-8 years were used in this study. The method used was direct sampling, which examined the qualitative and quantitative characteristics. The analytical methods used were descriptive analysis and qualitative analysis. The results show that the body length of female Bali cattle has an average of 104.75 cm, chest circumference has an average of 150.67 cm and a standard deviation of 8.72, the body height of female Bali cattle in this study had a minimum average of 80.75 cm, a maximum average of 144.25. The body colors consisted of brick red, brown, and yellowish brown. The horn shapes were U-shaped, curved backward, and curved downward. Vulva's color was black. Eel lines consist of thick, medium back lines and thin back lines. Further development of Bali cattle was required to improve production and reproductive performance so that performance could be the same as that of Bali cattle in their native region.